Development of mapping procedures using digital imagery derived from unmanned aerial vehicle system - Sidek, Faizatul Khadijah; Ahmad, Anuar (2008)
Digital photogrammetry is one of the important data source in GIS. Aerial photogrammetry is mainly used to produce topographic or thematic maps and digital terrain models. Digital images can be created by a variety of input devices and techniques, such as digital cameras, scanners, coordinate-measuring machines, seismographic profiling, airborne radar, and others. In aerial photogrammetry, the aerial photographs are acquired using a special camera known as metric camera or large format camera (230mm x 230mm) and fixed wing aircraft. Metric cameras have stable and precisely known internal geometries and very low lens distortions. Therefore, they are very expensive devices and the cost for acquiring aerial photographs is very expensive too. To acquire aerial photographs of a small area, it is not economical to use common large format aerial camera. Hence, other alternative has to be used. Nowadays, people from all around the world have started using small format camera for acquiring aerial photographs. In this study, the unmanned aerial vehicle (UAV) system in the form of very small airplane (2.7 kg) known as CropCam UAV (Canada) is used to acquire small format aerial photographs (i.e digital image) of an area for mapping. Sufficient number of ground control and check points are established using Global Positioning System around the studied area. The digital images are processed using digital photogrammetric system to produce photogrammetric output such as map or orthophoto. In this study, the mapping procedures between large format aerial photographs and small format aerial photograph are compared. In general, the mapping procedures of large format and small format camera are the same. For small format camera many photographs are required to cover the same area covered by large format camera. Hence, more time is required to produce the aerial photograph. However, small format camera has great potential to be used in various and diversified applications such as map revision of small area, crash accident on highway, land slide (environmental disaster), Geographic Information System (GIS) applications and others.